Airway surface liquid volume regulation determines different airway phenotypes in liddle compared with βENaC-overexpressing mice - Mall, Marcus A.; Button, Brian; Johannesson, Bjarki; Zhou-Suckow, Zhe; Livraghi, Alessandra; Caldwell, Ray A.; Schubert, Susanne C.; Schultz, Carsten; O'Neal, Wanda K.; Pradervand, Sylvain; Hummler, Edith; Rossier, Bernard C.; et al. (The journal of biological chemistry, 2010)
Studies in cystic fibrosis patients and mice overexpressing the epithelial Na+ channel β-subunit (βENaC-Tg) suggest that raised airway Na+ transport and airway surface liquid (ASL) depletion are central to the pathogenesis of cystic fibrosis lung disease. However, patients or mice with Liddle gain-of-function βENaC mutations exhibit hypertension but no lung disease. To investigate this apparent paradox, we compared the airway phenotype (nasal versus tracheal) of Liddle with CFTR-null, βENaC-Tg, and double mutant mice. In mouse nasal epithelium, the region that functionally mimics human airways, high levels of CFTR expression inhibited Liddle epithelial Nat channel (ENaC) hyperfunction. Conversely, in mouse trachea, low levels of CFTR failed to suppress Liddle ENaC hyperfunction. Indeed, Na+ transport measured in Ussing chambers (“flooded” conditions) was raised in both Liddle and βENaC-Tg mice. Because enhanced Na+ transport did not correlate with lung disease in these mutant mice, measurements in tracheal cultures under physiologic “thin film” conditions and in vivo were performed. Regulation of ASL volume and ENaC-mediated Na+ absorption were intact in Liddle but defective in βENaC-Tg mice. We conclude that the capacity to regulate Na+ transport and ASL volume, not absolute Na+ transport rates in Ussing chambers, is the key physiologic function protecting airways from dehydration-induced lung disease.
Gesehen am 03.05.2023